THE EFFECT OF THE NUMBERED HEADS TOGETHER (NHT) LEARNING MODEL ON SECOND GRADE STUDENTS’ EARLY READING SKILLS - Nani Jubaedah; Prabawati Nurhabibah; Widia Nur Jannag (Jurnal Cakrawala Pendas, 2026)
This study was motivated by the low early reading skills of elementary school students, particularly in the lower grades. There are still students who experience difficulty recognizing letters and reading syllables, words, and simple sentences, therefore a learning model is needed that can increase student engagement in the learning process. The research question in this study is whether there is a significant effect of the use of the Numbered Heads Together (NHT) learning model on the early reading skills of second-grade students at SDN 1 Megu Cilik. This study aims to determine the effect of the Numbered Heads Together (NHT) learning model on the early reading skills of second-grade students at SDN 1 Megu Cilik. The study employs a quantitative approach using a quasi-experimental method and a nonequivalent control group design. The research subjects consisted of 46 students, comprising 23 students in the experimental class and 23 students in the control class. Data collection techniques were conducted through observation, testing, and documentation. The results of the study showed that the average score of the experimental class increased from 51.74 to 77.87, while that of the control class increased from 47.83 to 69.57. The Mann-Whitney test yielded a significance value of 0.001, leading to the conclusion that the Numbered Heads Together (NHT) learning model has a positive effect on the early reading skills of second-grade students at SDN 1 Megu Cilik.